Cell volume regulation in cancer cell migration driven by osmotic water flow. Issue 8 (1st July 2019) - Morishita, Kazuhiro; Watanabe, Kengo; Ichijo, Hidenori
Abstract: Cancer metastasis is the most frequent cause of death for patients with cancer. The main current treatment for cancer metastasis is chemotherapy targeting cancer cells' ability to proliferate. However, some types of cancer cells show resistance to chemotherapy. Recently, cancer cell migration has become the subject of interest as a novel target of cancer therapy. Cell migration requires many factors, such as the cytoskeleton, cell‐matrix adhesion and cell volume regulation. Here, we focus on cell volume regulation and the role of ion/water transport systems in cell migration. Transport proteins, such as ion channels, ion carriers, and aquaporins, are indispensable for cell volume regulation under steady‐state conditions and during exposure to osmotic stress. Studies from the last 25 years have revealed that cell volume regulation also plays an important role in the process of cell migration. Water flow in accordance with localized osmotic gradients generated by ion transport contributes to the driving force for cell migration. Moreover, it has been reported that metastatic cancer cells have higher expression of these transport proteins than nonmetastatic cancer cells. Thus, ion/water transport proteins involved in cell volume regulation and cell migration could be novel therapeutic targets for cancer metastasis. In this review, after presenting the importance of ion/water transport systems in cell volume regulation, we discuss the roles of transport proteins in a pathophysiological context, especially in the context of cancer cell migration. Abstract : Cell migration is one of the most critical steps of cancer metastasis. Recent studies have revealed that cell volume regulation by osmotic water flow contributes to cell migration. We summarize the role of ion/water transport proteins in cancer cell migration from the point of view of cell volume regulation to provide novel therapeutic targets for cancer metastasis.